The Effect of Mulberry Leaves (Morus alba L) on Blood Pressure and Proteinuria in Rattus Norvegicus Wistar Strain Pre-Eclampsia Model - Tut Rayani Aksohini Wijayanti; Reny Retnaningsih; Rani Safitri (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2025)
Preeclampsia is a leading cause of maternal morbidity and mortality globally, including in Indonesia. It is characterized by hypertension and proteinuria, which appear after 20 weeks of pregnancy. The pathophysiology of preeclampsia is closely linked to oxidative stress, which is caused by abnormal placentation. One promising alternative treatment for managing preeclampsia is the use of natural ingredients with antioxidant properties, such as mulberry leaves (Morus alba). These leaves contain flavonoids, such as rutin and quercetin, which are known to have antioxidant effects. This study aims to examine the effects of mulberry leaf extract on blood pressure and proteinuria levels in male Wistar rats, using a preeclampsia model. The study employed a true experimental post-test only control group design. A total of 25 pregnant rats were randomly divided into five groups: a negative control group, a positive control group (which was induced with suramin to model preeclampsia), and three treatment groups receiving mulberry leaf extract at doses of 12.5, 25, and 50 mg/kgBW. Blood pressure and proteinuria levels were measured before and after 6 days of treatment. The results indicated that mulberry leaf extract significantly reduced both systolic and diastolic blood pressure and markedly lowered proteinuria levels. A significant relationship was observed between blood pressure and proteinuria (r = 0.528; p = 0.008), suggesting that the reduction in blood pressure was associated with a decrease in proteinuria. These findings suggest that mulberry leaf extract may be a promising natural complementary therapy for alleviating symptoms of preeclampsia, offering an alternative treatment approach to help manage this serious pregnancy complication. Further studies are needed to explore its potential in clinical applications.